A nasal omicron vaccine booster elicits potent neutralizing antibody response against emerging SARS-CoV-2 variants - Joy-Yan Lam; Yau-Yee Ng; Chun-Kit Yuen; Wan-Man Wong; Kwok-Yung Yuen; Kin-Hang Kok (Emerging Microbes and Infections, 2022)
SARS-CoV-2 has caused the COVID-19 pandemic since early 2020. As of January 2022, the worldwide spreading of SARS-CoV-2 leads to approximately 0.35 billion of human infections and five millions of deaths. Current vaccination is one of the effective ways to control SARS-CoV-2 transmission and reduce the disease severity. However, the antibody level against the immunogen significantly drops several months after the standard two-dose vaccination, and hence a third or fourth dose booster (the same immunogen) has been suggested to boost the antibody response. Here, we described an ultra-effective nasal vaccine booster that potently induced the extraordinary high-level of neutralizing antibody in pre-vaccinated mice. The vaccine booster is composed of a recombinant receptor binding domain of SARS-CoV-2 spike (either wild-type or omicron) fused with a domain of SARS-CoV-2 nucleoprotein. In the absence of adjuvants, a single intranasal administration of the booster in pre-vaccinated mice significantly induced systemic and mucosal antibody responses as evidenced by the elevation of the cross-variant neutralizing antibody and induction of IgA in bronchoalveolar lavage respectively. Most importantly, the single dose nasal vaccine booster (omicron version) potently enhanced the neutralizing activity against authentic SARS-CoV-2 omicron virus infection. Taken together, the induction of respiratory mucosal immunity and the enhancement of cross-variant neutralizing activity by the nasal vaccine booster warrants further clinical trials in humans.